Impact of Training Programme onÂ· the Adoption of Hygienic Practices in Peeling Sheds - C. Kappen, Daisy; P.S., Pushkaran (Fishery Technology, 2025)
Impact of the training programmes organised by Marine Products Export Development Authority, Cochin on hygienic measures to be followed in peeling sheds had been studied. The analysis showed that the training programme was effective in increasing the knowledge and the perception of peeling shed workers about the quality aspects. Among the trained peeling shed workers, the variables, viz., type of home and type of family had significant influence over the extent of knowledge possessed. Among the untrained workers education and extension orientation had significant influence on knowledge. Further, the selected 12 independent variableS had shown significant R2 values (0.4701 and 0.4182) towards the level of knowledge among the trained and untrained categories, respectively.